DICLOFENAC INDUCED ANGIOEDEMA: A CASE REPORT - Pise, Harshal Nutanrao; Padwal, Sudhir L. (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â Non-steroidal anti-inflammatory drugs (NSAIDs) are one of the most commonly prescribed groups of drugs for variety of indications. However, they are associated with many potential adverse drug reactions. The detailed information of these reactions is necessary to decrease the morbidity and mortality associated with these reactions. Angioedema can be caused by many etiological factors including drugs. The NSAID induced angioedema occurs infrequently but sometimes it may prove fatal if not treated promptly. The angioedema due to NSAIDs use may be caused due to increase in production of Leukotriene due block in cyclooxygenase pathway. The mast cells and to lesser extent basophils plays a major role in pathogenesis of angioedema. Early recognition and discontinuation of responsible NSAIDs should be done. Treatment with corticosteroids and antihistaminic is useful in management of angioedema. The author reports a case of a patient with angioedema in association with use of Diclofenac. Keywords: Angioedema, Diclofenac, Non-steroidal anti-inflammatory drugs, Leukotrienes.